2013
DOI: 10.1115/1.4025202
|View full text |Cite
|
Sign up to set email alerts
|

Blade Tip Shape Optimization for Enhanced Turbine Aerothermal Performance

Abstract: In high-speed, unshrouded turbines, tip leakage flows generate large aerodynamic losses and intense unsteady thermal loads over the rotor blade tip and casing. The stage-loading and rotational speeds are steadily increased to achieve higher turbine efficiency, and hence, the overtip leakage flow may exceed the transonic regime. However, conventional blade tip geometries are not designed to cope with supersonic tip flow velocities. A great potential lies in the modification and optimization of the blade tip sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The genetic optimizer CADO [24,25,26,27] was used in this work and is a differential evolution multi-objective optimization tool. The two selected optimization objectives were minimum mass flow averaged outflow entropy and maximum shaft power.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…The genetic optimizer CADO [24,25,26,27] was used in this work and is a differential evolution multi-objective optimization tool. The two selected optimization objectives were minimum mass flow averaged outflow entropy and maximum shaft power.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…11,12 It has found that the shape of blade tip has some relation with the leakage flow characteristics in the tip region of turbine rotors, 13 and some different types of winglets were designed and surrounded blade tip section to improve the tip flow structures of turbine blades, such as the winglets with tip overhang, with cavity, and with shaped features. 14 Based on the studies of tip winglet in turbine blades, it is noted that both the driving pressure difference near the blade tip and the leakage coefficient seem to be changed due to the winglet, which attributes to reduction of the strength of leakage flow and additional losses in the tip gap of rotors. 10,11,15 When the tip platform extension is used in turbine rotors or cascades, the winglet around the pressure side benefits to reduce the discharge coefficient of leakage flow and the pressure difference across the tip gap, and it eventually produces higher losses in the tip region, while the suction-side winglet produces fewer losses in comparison with the baseline.…”
Section: Introductionmentioning
confidence: 99%
“…The results have shown that the overall HTC on the squealer tip is higher than that near the PS and SS, and it is lower than that on the flat tip. De Maesschalck et al . (2014) presented a novel optimization of rotor tip profiles and found that the reduction of thermal load of the optimized tip shaper can be up to 40 percent, compared to the flat tip geometry.…”
Section: Introductionmentioning
confidence: 99%